Prevalence of Pulmonary Hypertension in End-stage Renal Disease Patients Undergoing Hemodialysis and Peritoneal Dialysis at a Referral Center in Mashhad, Iran, From 2015 to 2016 (Iranian Journal of Kidney Diseases, 2018)
Introduction. Pulmonary artery hypertension is a serious comorbidityof dialysis in patients with end-stage renal disease. The prevalence of dialysis-induced pulmonary artery hypertension is still a subject of debate. The aim of this study was to determine the prevalence of pulmonary artery hypertension in patients undergoing hemodialysis and peritoneal dialysis. Materials and Methods. This cross-sectional study was conducted on patients undergoing either hemodialysis or peritoneal dialysis in Montaserieh Dialysis Center in Mashhad, Iran during 2015 and 2016. Pulmonary artery pressure, ejection fraction, and serum levels of calcium, phosphorus, creatinine, and parathyroid hormone were measured. Results. A total of 50 patients (25 on hemodialysis and 25 on peritoneal dialysis) participated in the study. The mean age of the participants was 34 ± 12 years. The mean pulmonary artery pressure was significantly higher in the hemodialysis group compared to the peritoneal dialysis group (P < .001). Serum calcium was significantly higher in the peritoneal dialysis group compared (P = .04). Pulmonary artery hypertension was observed in 11 patients (22%), all of whom were in the hemodialysis group. There was a significant negative relationship between serum calcium and pulmonary artery pressure (P< .01). Hemodialysis was significantly related to higher pulmonary artery pressure (P < .001). Conclusions. This study revealed a high prevalence of pulmonary artery hypertension among end-stage renal disease patients undergoing dialysis. This study also found a novel significant negative relationship between serum calcium level and pulmonary artery pressure, and hemodialysis was found to be significantly related to higher pulmonary artery pressure.